Optically controlled E-MESFET for VLSI application - Bandhawakar G.; Pal B.B. (My University, 2025)
An enhancement mode MESFET (E-MESFET) is useful as a low voltage, low power device and plays an important role in VLSI designing. An E-MESFET behaves as a switch under optical illumination, it turns ON when light is ON and turns OFF when light is switched OFF. Studies have been made on optically controlled characteristics of an ion-implanted GaAs - MESFET which show that the drain source current can be enhanced with increasing photo voltage as well as radiation flux density. Effect of radiation becomes predominant over the impurity concentration. Sharp increase in drain to source current have been observed at flux density greater than or equal to 1020 / m2.